Updated WebGIS integrated in the Global Geo-informatics Options by Contexts (GeOC) Tool (French version). - Diwediga, Badabate; Le, Quang Bao; Jaspe, Jim; Fradi, Fajr; Bonaiuti, Enrico; Zucca, Claudio (2017)
This is the presentation of Dr. Badabate Diwediga during the workshop "Sustainable Land Management to Achieving Land Degradation Neutrality: Options-by-Context Approach and Tool", final workshop for the project "Impact Evaluation of SLM Options to Achieve Land Degradation Neutrality", held in Tunis on the 24th October 2017. This presentation highlights the new interfaces of the WEBGIS components of the GeOC tool.